Achilles tendon structure is associated with regular running volume and biomechanics - Jandacka, Daniel; Jandackova, Vera Kristyna; Juras, Vladimir; Vilimek, Dominik; Skypala, Jiri; Elavsky, Steriani; Uchytil, Jaroslav; Monte, Andrea; Hamill, Joseph (Journal of sports sciences, 2023)
Achilles tendinopathy was reported to have the highest incidence proportion of all running-related injuries. The purpose of this study was to analyse the association between the Achilles tendon structure and running activity status. 350 healthy participants (runners and inactive controls, 30-50 years) participated in this research. Each participant completed questionnaires: socioeconomic, psychological, physical activity habits, running status and history and VISA-A. Magnetic resonance imaging, anthropological, running biomechanics and 14 days of physical activity monitoring assessments were performed. There was a higher odd of being in the upper quartile of the Achilles tendon T2* relaxation time with higher maximal knee extension moment independent of age and sex. Compared with runners who ran 21-40 km per week, non-runners and those who ran more than 40 km per week had increased odds of having longest the Achilles tendon T2* relaxation time. Regular running of 21 to 40 km per week is related to the Achilles tendon T2* relaxation time indicating possibly better water content and collagen orientation in these runners with compare to inactive non-runners or highly active individuals. In addition, Achilles tendon T2* relaxation time as indirect indicator of the Achilles tendon structure was positively related to the maximal knee extension moment during running.
Keywords: Magnetic resonance imaging; Tendinopathy; běh; Achillova šlacha; tendinopatie; Humans; biomechanika; Sex; lidé; Knee Joint; Running; Achilles Tendon; kolenní kloub; Biomechanical Phenomena; T2* relaxation time; Middle age